2021
DOI: 10.1371/journal.pone.0260891
|View full text |Cite
|
Sign up to set email alerts
|

The implications of parent mental health and wellbeing for parent-child attachment: A systematic review

Abstract: Background Parent mental health and wellbeing may have implications for understanding attachment transmission. In this systematic review, we synthesise the published literature to determine the nature of the relationship between parent mental health and wellbeing and the intergenerational transmission of attachment and to provide recommendations for future research, clinical practice and intervention. Method Using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) approach, five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…(2021) reported that higher anxiety scores on the HADS related to lower certainty about mental states and higher pre‐mentalizing modes scores, with no association with interest and curiosity in mental states. Research on parental anxiety and PRF is lacking, as a recent systematic review highlighted (Risi et al., 2021), and it is therefore difficult to draw strong conclusions on the relation between these factors without further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) reported that higher anxiety scores on the HADS related to lower certainty about mental states and higher pre‐mentalizing modes scores, with no association with interest and curiosity in mental states. Research on parental anxiety and PRF is lacking, as a recent systematic review highlighted (Risi et al., 2021), and it is therefore difficult to draw strong conclusions on the relation between these factors without further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The influences of parent wellbeing on the parent–child dyad [ 1 , 2 , 3 ] and early child development [ 4 , 5 , 6 ] have been explored extensively in the general population. The most commonly researched parent wellbeing indicators include parental depression [ 7 ], trauma [ 8 ], problem gambling [ 9 ], and parental stress [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…An expanding body of qualitative research on Indigenous wellbeing argues that the conceptualisation of wellbeing extends beyond this deficit-focus and should include positive wellbeing [ 23 ]. However, little is known about the contemporary conceptualisation of parent wellbeing, how its constructs might influence parents’ and child-specific outcomes, and if these constructs are sensitive to change in response to parent interventions [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted with parents of typically developing children informs us that if a parent has a mental health difficulty, they may have to rely on their child to take on ageinappropriate responsibilities (Aldridge and Becker, 2003) with their own needs overshadowing the vulnerability of their offspring (Monds-Watson et al, 2010). We know from research in this field that poor parental mental health is associated with child behavioural difficulties (Mowbray et al, 2006) and can impact parent-child attachment (Risi et al, 2021) with insecure attachment contributing to the development of mental health disorders (Mikulincer and Shaver, 2012). With this in mind, it could be hypothesised that having a child with LD, could impact the mental health of parents, which could then overshadow the vulnerability of the individual with LD who may then develop their own mental health difficulties.…”
Section: Introductionmentioning
confidence: 99%